Understanding the Need for Change in LGBTQIA+ and Unmarried Couple's Rights in India by Observing their Legal Limitations and Rights: A Comparative Study - Kuttappan, Seethal; Tiwana, Dalliandeep Kaur; Thakur, Deepika (International Journal of Membrane Science and Technology, 2023)
This article compares the legal protections and rights now in place for LGBTQ(QUEER) and unmarried couples to those of the straight couples. They are prevented from taking use of several legal benefits like compensatory rights, educational and insurance welfare programs, etc. for the offspring due to the misidentification of Queer couples and the unmarried pair within the definition of a legally married couple. This illegal prejudice is shown in order to reconsider and provide them equal legal protections under the protection of the right to life guaranteed by Article 21 of the Indian Constitution. The researcher conducted a comparative analysis of the laws of several nations. The article also emphasizes the necessity of enhancing the current legal and legislative framework in our nation. By analyzing many situations and reviewing current literature to identify the gaps, the researcher chose qualitative and doctrinal research methodologies.